Artefactually low glycated haemoglobin in a patient with severe hypertriglyceridaemia. Issue 5 (1st May 2003) - Garrib, A; Griffiths, W; Eldridge, P; Hatton, R; Worsley, A; Crook, M
Abstract : This report describes a case of artefactually low glycated haemoglobin (Hb) in a patient with type II diabetes and severe hypertriglyceridaemia. The effect of hypertriglyceridaemia on glycated Hb determination using the Abbott Vision method was investigated in a series of patients with diabetes. The interference of triglycerides in glycated Hb assays was also investigated by two other methods, the Beckman Synchron CX4 delta immunoturbidimetric method, and the Primus affinity chromatography high performance liquid chromatography assay.